"It doesn't exist, only other people have it, or it's bad luck": perceptions of HIV as barriers to its prevention in Bata - C. Rodríguez-Reinado; T. Blasco-Hernández; N. Abeso; A. Benito-Llanes (BMC, 2023)
Abstract Background Currently, Africa is the region of the world where the highest number of new cases of HIV infection are registered. In 2022, Equatorial Guinea was the Central African country with the highest HIV prevalence (6.9%) and incidence (3.80 per 1,000 amongst the population of all ages). The main objective of this study was to determine the perceptions of HIV and the meanings given to it among the population of Equatorial Guinea in order to assess to what extent they represent a barrier to the prevention strategies implemented hitherto. Methods A total of 30 semi-structured interviews and nine focal groups were carried out. Findings The interviewees' testimonies revealed a combination of differing perceptions and meanings around HIV. In some cases, HIV was perceived as "a non-existent illness", and in others as "a disease of others", or as "a disease of bad luck". Other majority perceptions of HIV classed it as "a deadly disease" or "a sexual illness". Conclusions All these perceptions of HIV and the social representations constructed around it can represent a barrier to adopting preventive practices. Hence, in order to improve efficacy, efficiency, and effectiveness, it is recommended that HIV prevention policies take into account the heterogeneity of meanings linked to the different social groups that have contracted the virus.